2022
DOI: 10.3390/su142013413
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Risk of Failure from Ceramic-on-Ceramic Total Hip Prosthesis by Selecting Ceramic Materials Based on Tresca Stress

Abstract: The choice of ceramic-on-ceramic coupling in total hip prosthesis has advantages over couplings with other combinations of materials that use polyethylene and metal materials in terms of high hardness, scratch resistance, low wear rate, and increased lubrication performance. To reduce the risk of primary postoperative failure, the selection of ceramic materials for ceramic-on-ceramic coupling is a strategic step that needs to be taken. The current study aims to analyze ceramic-on-ceramic coupling with commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 44 publications
0
85
0
Order By: Relevance
“…Appropriate mechanical properties are conducive to the transportation and application of the occluder in the body and ensure the integrity of the membrane to block blood flow. There are many evaluation methods used to characterize these materials [ 19 ]. In this study, we used the tensile strength test.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate mechanical properties are conducive to the transportation and application of the occluder in the body and ensure the integrity of the membrane to block blood flow. There are many evaluation methods used to characterize these materials [ 19 ]. In this study, we used the tensile strength test.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Saito et al [ 2 ] observed different outcomes in patients with knee OA with or without foot pain after total knee arthroplasty. In addition, finite-element-based computational approaches can be considered in future study designs to reduce the cost and obtain a detailed plantar stress distribution through the model [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 63 ] No motion Full cycle divided into 32 phases Ammarullah et al. [ 50 , 72 ] ABAQUS v. 6.14–1 Total hip arthroplasty Tresca stress Simplified walking condition 3D load Bergmann et al. [ 63 ] No motion Full cycle divided into 32 phases Barreto et al.…”
Section: Computational Simulation Study On Bearing Of Hip Joint Prost...mentioning
confidence: 99%